Pembelajaran Kontekstual Untuk Mengembangkan Kemampuan Komunikasi Dan Pemecahan Masalah Matematika Siswa Sekolah Menengah Pertama - Maryati, Iyam (Pasundan Journal of Mathematics Education : Jurnal Pendidikan Matematika, 2013)
This study focuses on revealing comparison of communication skills and mathematical problem solving junior high school students, as a result of the use of contextual learning and conventional learning in mathematics learning. Subjects in the study were students of class VIII junior secondary school class one experimental and one control class. The instrument used in this study consists of two instruments, namely, 1) test communications and mathematical problem solving that aims to measure communication skills and mathematical problem solving of students after learning, and 2) the scale of attitude that serves to express students' applied learning the class eksperimen.Berdasarkan data analysis in this study, it is concluded that 1) the ability of students in mathematical communication in the group of students that uses contextual learning better than students who studied with conventional learning. 2) The ability of students in mathematical problem solving in student groups that use contextual learning better than students who studied with conventional learning. 3) There is a very high correlation between communication skills and mathematical problem solving of students. This means that the rank obtained by the students on communication skills with a rating similar to that obtained in mathematical problem solving ability. There are also associations at anatara enough communication skills to solving mathematical problems. This shows that student achievement in communication skills similar to mathematical problem solving ability and vice versa. Correlations and associations found in both groups. 4) the scale of students' attitudes toward learning context shows that the majority of students expressed agreement the learning activities that took place during the study.